Consumption of bottled water by children in the city of Bauru, State of São Paulo, Brazil - A brief communication - Ramires, Irene; Grec, Roberto H. C.; Moura, Patrícia G.; Pessan, Juliano Pelim [UNESP]; Lauris, José R. P.; Buzalaf, Marília A. R. (Wiley, 2007)
Objectives: To determine the consumption of bottled water by children in the city of Bauru, State of São Paulo, Brazil. Methods: A stratified sample of the 17 areas established by the city plan was used to identify a total of 1,000 homes for visitation. Information was collected using a questionnaire concerning the type of water consumed and population demographics. Results: Overall, around 30 percent of all residences used bottled water. Among all households where bottled water was consumed, about 26 percent had children residing. For those with children and bottled water, 81 percent reported to use bottled water for the preparation of the children's foods and beverages. Conclusions: An important percentage of children consume bottled water in the city of Bauru, State of São Paulo, Brazil. Considering previous studies showing that fluoride concentrations vary in bottled water, public health measures should be implemented in order to guarantee adequate levels of fluoride in commercialized water. © 2007, American Association of Public Health Dentistry.
Keywords: Bottled water; Children; Fluoride; Fluorosis; anticaries agent; fluoride; mineral water; Brazil; child; conference paper; human; packaging; questionnaire; social class; utilization review; Cariostatic Agents; Child; Fluorides; Humans; Mineral Waters; Product Labeling; Questionnaires; Social Class